MANAGEMENT HIFDZIL AL-QUR'AN IN IMPROVING SANTRI'S MEMORIZATION IN ISLAMIC BOARDING SCHOOLS - Ishomuddin, Kholid; Rizquha, Ach; Mubaroq, Muhammad Syahrul (Managere: Indonesian Journal of Educational Management, 2023)
The research focuses on investigating the strategies and management applied in the Hifdzul Al-Qur'an program at two Islamic educational institutions, namely the Nurul Jadid Paiton Islamic Boarding School and the Nurul Qodim Kalikajar Islamic Boarding School. The primary aim of the research is to comprehensively understand how these boarding schools plan their Quranic memorization strategies. The research methodology employed a qualitative case study approach. The researcher utilized purposive sampling to engage various stakeholders such as regional heads, tahfidz administrators, students, guardians, and the local community in in-depth interviews. The findings revealed that both boarding schools have structured planning focusing on Quranic memorization techniques and comprehensive learning activities. The implications drawn from this research on the management of Hifdzul Al-Qur'an in Islamic boarding schools hold substantial significance for educational practices and institutional development.